An Optimal Load Balancing Strategy for Virtual Machines in Cloud Environment - Dubey, Megha; Chauhan, Pradeep Singh (International Journal of Computer Sciences and Engineering, 2018)
Cloud computing is rising as a leading edge that delivers secure data storage center, unlimited computational resources, network connection and flexible data processing capabilities. The main aim of cloud data centers is how to distribute and maintain the tasks coming from request group efficiently and accurately. Load balancing is one of the major issues in cloud computing which stabilizes the dynamic workload evenly spread across all the virtual machines (VMs) of the cloud data centers. It helps to upgrade the performance of the cloud system and make proper utilization of resources by legitimate allocation. This paper focuses on developing hybrid load balancing algorithm which disseminates the arriving requests in cloud data centers. The proposed algorithm will be implemented using Cloud Analyst simulator and the performance of this algorithm will compare with Throttled, Round Robin and ESCS (equally spread current execution) algorithms on the basis of overall response time and data center processing time. The analysis carried out in the paper shows that the proposed algorithm performs better than the existing algorithms.